Legal Rights And Protections For Lgbtqia+ Individuals (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Focusing on the seminal National Legal Services Authority v. Union of India (2014) decision and following developments, this essay critically evaluates the judicial attitude towards transgender rights in India. By establishing transgender people as a distinct "third gender," the NALSA ruling upheld the fundamental rights of transgender people to self-determination, recognition, and equality. Cases like Ms. S. Sushma v. Commissioner of Police and Arun Kumar v. Inspector General of Registration show how the court has moved forward in protecting LGBTQIA+ rights and outlawing conversion therapy and other forms of discrimination. Additionally, the research examines the 2019 Transgender Persons (Protection of Rights) Act, assessing its effects and shortcomings in guaranteeing real equality. Transgender people still face structural impediments and social stigma that prevent them from fully realizing their rights, even if the law has made progress in this area. At the conclusion of the article, it is emphasized that the court plays a crucial role in modern India in advancing gender justice, constitutional morality, and inclusivity.